Hybrid Messaging Architecture and Interfacing Scheme - Min, Kyoung Jun; Bae, Min Ho; Park, Gyu Dong; Oh, Sang Yoon (Journal of Korean Institute of Communications and Information Sciences, 2020)
Publish-subscribe messaging paradigm is a popular event dissemination model for tactical communication environment and IoT communication environment. However, when it is applied to WAN, the network can suffer from either scalability problem caused by high network traffic to maintain auto-discovery capability for P2P or fault-tolerance problem caused by a single-point of failure issue of a broker. A hybrid m;essaging system architecture is proposed to resolve these problem, however the proposed architectures so far are integrations where P2P is the core and the other is attached to it. Thus, the current hybrid messageing architectures are limited to fully utilize benefits of hybrid architecture. In this paper, we proposed a hybrid messaging architecture where two messaging systems are integrated equally focused. In this proposal, we also proposed a interfacing scheme with API and queue to provide loosely coupled interfacing as well as a scheme to topic integration. We build a prototype with P2P based DDS and a broker based MQTT standard to evaluate the effectiveness of our proposed architecture and schemes.
Keywords: broker messaging; interfacing; message queue; P2P messaging; Publish-subscribe paradigm